Zinc ion battery negative electrode material with stripe array as well as preparation method and application of zinc ion battery negative electrode material

By etching on the crystal surface of the zinc foil (002) to form a striped array, the problems of dendrite growth and hydrogen evolution reaction of zinc metal anode in aqueous zinc ion batteries were solved, and the electrochemical performance and cyclic stability of the battery were significantly improved.

CN119876955APending Publication Date: 2025-04-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510071081.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The zinc metal anode faces problems such as surface dendrites growth, hydrogen evolution reaction and side reactions in aqueous zinc-ion batteries, resulting in battery short circuits, reduced Coulomb efficiency and reduced electrochemical activity, hindering the commercial use of batteries.

Method used

By etching the (002) crystal surface surface of zinc foil to form a striped array, the specific surface area of ​​the anode material is increased, the regional current density and electric field density are reduced, the corrosion of aqueous electrolyte and hydrogen evolution reaction are suppressed, and the electrode/electrolyte interface is stabilized.

Benefits of technology

Effectively inhibit dendrites' growth and hydrogen evolution reaction, improve the electrochemical performance and cycle stability of the battery, and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876955A_ABST
    Figure CN119876955A_ABST
Patent Text Reader

Abstract

The invention discloses an anode material for an ion battery as well as a preparation method and a finished product of the anode material, and belongs to the field of ion batteries. The method for manufacturing the anode material of the zinc ion battery comprises the following steps of: fixedly soaking a zinc foil with a (002) crystal face facing upwards in an etching solution subjected to ultrasonic treatment to etch the surface so as to form a stripe array; through the mode, high-quality manufacturing can be realized, dendritic crystal growth of the anode material in the use process of the ion battery can be effectively inhibited, and meanwhile, side reactions on the surface of the anode material can be greatly reduced, so that the use performance of the anode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ion batteries, and in particular, the present invention relates to an anode material for ion batteries and a preparation method and a finished product thereof. Background Art

[0002] With the continuous development of new energy technologies, large-scale electric energy storage technology has attracted widespread attention from researchers.

[0003] Among aqueous rechargeable batteries, aqueous zinc-ion batteries (AZIBs) have become one of the most promising candidate materials for the next generation of large-scale energy storage systems due to their safety, low cost and environmental friendliness.

[0004] However, in aqueous zinc-ion batteries, the zinc metal anode faces a severe challenge of surface dendrite growth. Uncontrolled dendrite growth on the anode surface can cause the separator to pierce, leading to a short circuit in the battery.

[0005] In addition, the hydrogen evolution reaction (HER) caused by the formation of active water molecules and byproducts at the electrode-electrolyte interface (EEI) leads to a decrease in the Coulombic efficiency (CE) and hinders the deposition kinetics of zinc, thereby reducing the electrochemical activity of the battery.

[0006] In summary, dendrite growth, hydrogen evolution and side reactions of zinc metal anodes hinder the further commercial use of aqueous zinc-ion batteries. Summary of the invention

[0007] The examples of the present invention provide an anode material for an ion battery, a preparation method and a finished product thereof, with the aim of effectively alleviating problems such as dendrites and hydrogen evolution side reactions during the use of the ion battery.

[0008] The exemplary solution of the present invention is implemented as follows.

[0009] A method for manufacturing anode materials for zinc ion batteries comprises: immersing a zinc foil with a surface having a (002) crystal plane facing upward in an etching solution under ultrasonic treatment to etch the surface to form a stripe array.

[0010] A zinc ion battery anode material obtained by implementing the method, wherein the anode material has a stripe array uniformly formed on the (002) crystal plane, and the stripes have clear contours.

[0011] An ion battery anode material comprises an anode metal foil, the surface of which has a selected crystal plane determined by the element composition of the anode metal, and the crystal plane is formed with a nanometer fine structure.

[0012] A manufactured product includes the above anode material.

[0013] Compared with the prior art, in the examples of the present invention, the zinc foil is fixedly immersed in an etching solution under ultrasonic treatment with the surface having the (002) crystal plane facing upward to etch the surface to form a stripe array.

[0014] By forming a stripe array, the specific surface area of ​​the anode material can be increased, the regional current density that limits dendrite growth can be reduced, the electric field density can be uniform, the corrosion and hydrogen evolution of the aqueous electrolyte can be inhibited, the electrode / electrolyte interface can be stabilized, and the electrochemical performance of the battery can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] For a clearer explanation, the following briefly introduces the drawings required for the description.

[0016] Figure 1 The SEM comparison pictures of the electrode materials at different magnifications in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4 are shown; Figure 2 Symmetrical cells assembled from zinc electrode sheets in Examples 1, 2, 3 and Comparative Examples 1 and 2 were charged at a current density of 1 mA cm -2 and the deposition surface capacity is 1 mAh cm -2 The cycle curve of stripping / plating is shown below; Figure 3 The symmetrical battery assembled with the zinc electrode sheet in Example 1 was tested at a current density of 0.5 mA cm-2 and a deposition surface capacity of 0.2 mAh cm -2 The cycle curve of stripping / plating is shown below; Figure 4 The chronoamperometry diagram of the symmetrical battery assembled with the zinc electrode sheets in Example 1 and Comparative Example 1 at an overpotential of -150 mV; Figure 5 The EIS curves of the symmetrical cells assembled with zinc electrode sheets in Example 1 and Comparative Example 1; Figure 6 The half-cell LSV curves of the zinc electrode sheets assembled in Example 1 and Comparative Example 1; Figure 7 CV curves of the full battery in ZFA-1@Zn / / zinc salt / / manganese base in Example 1 and Zn / / zinc salt / / manganese base in Comparative Example 1; Figure 8The charge and discharge cycle curves and cycle efficiency of the full battery in ZFA-1@Zn / / zinc salt / / manganese base in Example 1 and Zn / / zinc salt / / manganese base in Comparative Example 1. DETAILED DESCRIPTION Side reactions such as dendrites and hydrogen evolution seriously affect the application of ion electrons. Therefore, it is necessary to focus on controlling them. In order to achieve the above purpose, in the present invention, the microscopic morphology of the anode metal of the ion battery is optimized and improved.

[0017] Specifically, in the examples of the present invention, the surface of the anode metal of the anode material of the ion battery is selected to have a nano-fine structure formed on a selected crystal plane of the anode metal.

[0018] That is, the present invention forms a stripe array with preferential crystal planes by etching the surface of zinc foil (also discussed as an operation with the same function of modification / acid etching in some subsequent descriptions), thereby slowing down side reactions such as dendrites and hydrogen evolution, and forming a zinc ion battery anode material with suppressed side reactions.

[0019] The selected crystal plane can induce the metal growth direction on the anode metal surface, slow down the corrosion rate of the electrolyte, and reduce the metal deposition in the vertical direction, thereby effectively inhibiting the formation of dendrites, stabilizing the electrode / electrolyte interface, and improving the cycle performance of the battery. At the same time, the nano-fine structure can increase the specific surface area of ​​the electrode material and reduce the local current density, thereby providing a more uniform nucleation site, inducing uniform deposition of zinc ions, reducing the polarization voltage, and slowing down the growth of dendrites.

[0020] The selection of the crystal plane of the anode metal depends on the elemental composition of the anode metal so as to control the growth direction of the metal on the surface of the anode metal. For example, for a zinc ion battery, in the zinc ion anode material, the anode metal is zinc, and can be a zinc plate or a zinc sheet. Accordingly, the aforementioned crystal plane is (002).

[0021] As for nano-fine structures, they can be various microscopic structures.

[0022] The microstructure can have a nanoscale structural size and is regularly arranged, which means that in its microscopic morphology (such as shown by electron microscope images), structures with repeated distribution can be found, such as micro- and nano-sized holes, grooves, fibers, protrusions, patterns, stripes, etc.

[0023] In some examples, the nano fine structure can be a nano array structure, that is, a nano structure distributed in an array form. Optionally, for zinc ion battery anode materials, the array structure is composed of stripes distributed in an array, that is, nano structure nano stripes.

[0024] Therefore, in some examples of the present invention, a zinc ion battery anode material is disclosed. The anode material is mainly composed of zinc foil, and the (002) crystal plane of the zinc foil is formed with a stripe array.

[0025] The stripe array can be formed on one surface or both surfaces of the zinc foil. According to the structural characteristics of the ion battery, preferably, the stripe array is formed on one surface of the zinc foil.

[0026] In order to facilitate those skilled in the art to implement the solution of the present invention, a method for manufacturing anode materials for zinc ion batteries is also disclosed in the examples.

[0027] Mainly, the method for manufacturing anode material for zinc ion battery comprises: forming a stripe array on the (002) crystal plane of the surface of zinc foil.

[0028] In some examples, the above stripe array can be realized by additionally growing material on the surface of the anode metal, or by microscopically “carving” the surface of the anode metal.

[0029] In an example of the present invention, the stripe array is formed on one surface of the zinc foil (described as the front side) by etching, and the other surface of the zinc foil is not etched.

[0030] The other surface is not etched by shielding the other surface. The shielding method may be to coat the other surface with a reagent to isolate the etching operation from the surface.

[0031] The reagents may vary depending on the type of etching operation. That is, the coating reagent is selected according to the method of etching operation or the material used. For example, in some examples, the method of shielding the other surface (which may also be described as the back side) of the zinc foil is to attach a polymer to the other surface. For example, a polymer material is coated on the other surface and cured to form a protective layer / protective layer of an organic component; and this can be done before immersing the zinc foil in the etching solution.

[0032] Optionally, the etching is carried out by acid etching. In order to avoid the adverse effects of dirt, oxide layer, etc. on the zinc foil surface, preferably, the surface to which the stripe array is attached can be pre-treated to remove the oxide layer and organic phase on the surface.

[0033] The acid etching method may be to apply the acid solution to the surface of the zinc foil by brushing or dripping the acid solution. In other examples, the acid etching may also be to immerse the zinc foil in the acid solution. Preferably, during the acid etching process, the acid solution is simultaneously subjected to ultrasonic treatment. Through the synergistic effect of the etching reaction and the ultrasonic treatment, a stripe array with clear and uniform etching can be obtained.

[0034] In addition, acid etching can achieve a replacement reaction, that is, the acid reacts with the anode metal to produce gas (such as hydrogen). Therefore, optionally, the zinc foil is fixedly immersed in the acid solution and combined with ultrasonic treatment to eliminate the adverse effects caused by the large amount of hydrogen produced by the etching reaction.

[0035] This is based on the consideration that the etching reaction (acid etching) will produce a large amount of hydrogen. And the generated hydrogen will accumulate on the surface of the zinc foil in large quantities, thereby affecting the progress of the etching reaction and causing the etching reaction to be interrupted. Then, by performing ultrasonic treatment while the etching reaction is in progress, the ultrasound can be used to make the hydrogen quickly leave the surface of the zinc foil due to the effect of the ultrasound, avoiding the accumulation of hydrogen on the surface of the zinc foil, thereby ensuring that the reaction solution is in contact with the zinc foil (rather than being isolated by hydrogen) to keep the reaction going.

[0036] In some cases, the acid used in the etching is a medium-strong acid (with an ionization constant Ka of, for example, 10 -1 ~10 -4 The strong acid includes, but is not limited to, one or more of phosphoric acid, tartaric acid, sulfurous acid, pyruvic acid, oxalic acid, and nitrous acid.

[0037] In a specific optional example, phosphoric acid is used for acid etching, and the concentration of phosphoric acid is optionally 50wt% to 85wt%; accordingly, the polymer includes polyimide. The etching reaction time can be controlled to 30s to 1200s (seconds) to control the thickness, depth and other structural parameters of the stripe array.

[0038] In a more specific example, the method for preparing a zinc ion battery anode material having a stripe array can be briefly described as: using zinc foil as a substrate, protecting the lower surface of the zinc foil and etching the upper surface of the zinc foil with a medium-strong acid to form a stripe array.

[0039] For example, Step 1) pre-treating the zinc foil and protecting the lower surface of the zinc foil; Step 2) etching the upper surface of the zinc foil with a medium-strong acid to form a stripe array; Step 3) After the etching process is completed, the etched zinc foil is washed and dried in sequence.

[0040] The specific steps of preprocessing in step 1) are as follows: Step 1. Cut the zinc foil.

[0041] In the second step, the cut zinc foil is sequentially soaked in acid solution, ultrasonicated, washed and dried; the acid solution used for soaking is hydrochloric acid solution with a concentration of 0.1-0.5 mol / L; the washing is rinsed with an organic solvent (which can be C2H6O / ethanol, which is volatile and can make the surface of the zinc foil dry quickly). The oxide layer and oil stains on the surface of the zinc foil are removed by soaking, ultrasonication and washing, and the ultrasonication (which can last for 0.5 hours) is used to treat impurities on the surface of the material and residues on the surface of the zinc foil after pickling.

[0042] Step 3: Protect the lower surface of the dried zinc foil. In one embodiment, a polyimide tape is attached to one side of the zinc foil (i.e., the lower surface of the zinc foil) for protection.

[0043] In step 4, the protectively treated lower surface of the zinc foil is fixed in a reaction vessel (e.g., with a diameter of 90 mm), and the zinc foil is immersed in a medium-strong acid, and the immersion time can be 30 seconds to 1200 seconds.

[0044] For example, a well-protected zinc foil is fixed in a reaction vessel with the side participating in the etching reaction facing upward (i.e., the upper surface of the zinc foil). The etching reaction will produce a large amount of hydrogen. One side of the zinc foil substrate is protected and fixed in a glass container to prevent this side from participating in the etching reaction and producing a large amount of H2 to lift the zinc foil out.

[0045] After the etching reaction is completed, the zinc foil is taken out with tweezers and repeatedly rinsed with deionized water to remove the H3PO4 solution and surface residues on the surface of the zinc foil.

[0046] Then rinse with C2H6O and put it into a vacuum drying oven for drying. The drying temperature is controlled at 50℃~70℃ and the drying time is 8~12h. Using C2H6O to clean is volatile and can make the surface of zinc foil dry quickly. Vacuum drying prevents the obtained material from reacting with oxygen and being oxidized.

[0047] The surface morphology of the zinc ion battery anode material obtained in this way is a stripe array. The formation of the stripe array can increase the specific surface area of ​​the electrode material, make the electric field distribution on the zinc foil surface more uniform, and provide more uniform nucleation sites, so that zinc ions can be induced to deposit uniformly on the zinc foil surface during battery use, thereby reducing the polarization voltage and slowing down the growth of dendrites.

[0048] In some examples of the present invention, the battery is assembled (1-4M ZnSO4 is used as the electrolyte), and the actual current density can reach 0.2-5 mA cm -2 The deposition surface capacity can reach 0.5-2 mAh cm -2 .

[0049] On this basis, the example also discloses an application example of the above anode material, that is, the example discloses a finished product, which includes the above anode material. Optionally, the finished product is an electrode slurry, an electrode sheet, a battery, or a power source; or, the finished product includes a container, and a power source contained in the container and made of the anode material.

[0050] In combination with the above, the solution of the present invention can have the following effects: 1. The raw materials used in the preparation method are widely available, environmentally friendly, safe and pollution-free, and the preparation process is simple, so the process cost is low and has good application prospects for zinc ion batteries.

[0051] 2. The present invention adopts a replacement reaction (acid-metal reaction) to react on the surface of zinc foil. The method is simple and convenient, simplifies the experimental steps, and shortens the preparation time of the negative electrode material of the aqueous zinc ion battery.

[0052] 3. The present invention uses medium-strong acid etching to prepare a stripe array surface with a (002) crystal plane on the surface of the zinc foil. Medium-strong acid etching on the zinc foil can obtain a stripe array with obvious length and width in a relatively short time, and the depth between the stripes is relatively deep.

[0053] In particular, the stripe array can increase the specific surface area of ​​the electrode material, reduce the local current density, and thus provide more uniform nucleation sites, inducing uniform deposition of zinc ions, reducing the polarization voltage, and slowing down the growth of dendrites.

[0054] In addition, the (002) crystal plane of zinc can induce the parallel growth of zinc metal, slow down the corrosion rate of the electrolyte, and prevent zinc ions from being deposited in the form of vertical dendrites on the surface of zinc foil, thereby effectively inhibiting dendrite formation, stabilizing the electrode / electrolyte interface, and improving the cycle performance of the battery.

[0055] In summary, the present invention adopts a simple replacement reaction, takes zinc foil as a substrate, and uses a medium-strong acid H3PO4 to etch the surface of the zinc foil. The morphology of the zinc foil surface is controlled by controlling the reaction time. By protecting one side of the zinc foil and fixing it in a reaction vessel for coordinated ultrasonic treatment, the adverse effects caused by a large amount of hydrogen generated by the etching reaction are eliminated, and the other side of the zinc foil is etched to obtain a clearly etched striped zinc foil surface morphology.

[0056] The formation of the stripe array can increase the specific surface area of ​​the electrode material, make the electric field distribution on the zinc foil surface more uniform, provide more uniform nucleation sites, induce zinc ions to deposit uniformly on the zinc foil surface, reduce the polarization voltage, and slow down the growth of dendrites.

[0057] At the same time, the (002) crystal plane of zinc ions can induce the parallel growth of zinc metal, slow down the corrosion rate of the electrolyte, and reduce the tip effect on the surface of the zinc foil, thereby effectively inhibiting the deposition of zinc ions on the surface of the zinc foil in the form of vertical dendrites, effectively improving the service life and cycle performance of the battery.

[0058] Several specific embodiments are given below.

[0059] Example 1 1. Preparation of negative electrode materials Cut the zinc foil into 5cm×5cm zinc sheets, flatten it, soak it in hydrochloric acid for 30s to remove the oxide film and impurities on the surface, and the concentration of hydrochloric acid is 0.1mol / L. The soaking time should not be too long to avoid reducing the thickness of the zinc foil. Take out the zinc sheet after ultrasonic treatment, wash it repeatedly with anhydrous ethanol and deionized water to remove the hydrochloric acid on the surface, dry it in a natural environment, and use it as a substrate for later use.

[0060] Protect one side of the dried zinc foil to ensure that it does not participate in the etching reaction. Specifically, a polyimide tape is attached to the lower surface of the zinc foil for protection, and the protected zinc foil is fixed in the culture dish with tape, with the side participating in the reaction facing up (i.e., the upper surface of the zinc foil), and the zinc foil is kept flat. Protect well in the fume hood, use a glass measuring cylinder to measure 50mL of H3PO4 solution, wherein the concentration of the H3PO4 solution is 85%, pour the measured H3PO4 solution into the culture dish, and ensure that the upper surface of the zinc foil is completely immersed in the H3PO4 solution, and start timing, control the reaction (etching treatment) time to 5min, and perform ultrasonic treatment while etching. During the reaction, ultrasound helps to prevent the generated H2 from completely covering the upper surface of the zinc foil, resulting in the isolation of the zinc foil from H3PO4, so that the etching treatment can be carried out more efficiently, so that the stripe morphology is more obvious and controllable. At the same time, ultrasonic treatment allows H2 to dissipate and discharge quickly, avoiding the generation of induction gas to lift the zinc foil out of the solution surface, interrupting its reaction. When the reaction time is reached, the zinc foil is quickly taken out, and the surface of the zinc foil is repeatedly rinsed with deionized water to remove the residual H3PO4 and other reaction products on the surface, and then rinsed with C2H6O. After rinsing, it is placed in a vacuum drying oven for drying. The drying temperature is controlled at 60°C and the drying time is 12 hours. Finally, the zinc ion battery anode material with an etched stripe array is obtained, which is recorded as ZFA-1.

[0061] In this embodiment, a polyimide tape is firstly attached to one surface (lower surface) of the zinc foil to protect the zinc foil and prevent the zinc foil from being lifted out by a large amount of H2 generated by the etching reaction. In addition, the ultrasonic treatment during the etching process causes the generated hydrogen to quickly leave the surface of the zinc foil, and it is difficult for the hydrogen to accumulate in large quantities on the surface of the zinc foil and affect the etching of the surface of the zinc foil.

[0062] This example uses a simple replacement reaction and ultrasonic synergistic treatment to etch the surface of the zinc foil to form a stripe array on the surface of the zinc foil. The experimental steps are simple, the repeatability is high, the time for synthesizing the negative electrode material is greatly shortened, and the experimental method has good universality. The obtained ZFA-1 has a uniform morphology and clear stripes.

[0063] 2. Assemble the battery The prepared zinc negative electrode material ZFA-1 was cut into electrodes with a diameter of 12 mm using a slicer. Two identical electrodes were selected, one of which was placed in the positive electrode shell, and the unetched side was in contact with the positive electrode shell. A glass fiber diaphragm was placed, and 120uL 2M ZnSO4 was dripped as an electrolyte using a pipette. Then another electrode was placed on top of the diaphragm, and the unetched side was also in contact with the stainless steel gasket. Then the gasket and shrapnel were placed in turn, and finally the negative electrode shell was buckled on. The battery was packaged using a battery packaging machine to obtain a modified zinc negative electrode aqueous zinc ion symmetrical button battery, marked as ZFA-1@Zn / / ZFA-1@Zn symmetrical battery.

[0064] As above, the prepared material was cut into electrodes with a diameter of 12 mm using a slicer, and the copper foil and the electrodes cut from the etched ZFA-1 were used as the positive and negative electrodes. The copper foil was placed in the positive electrode shell, and the glass fiber diaphragm was placed. 120uL of 2M ZnSO4 was dripped as the electrolyte using a pipette, and then a negative electrode electrode cut from ZFA-1 was placed on top of the diaphragm, so that the unetched side was in contact with the stainless steel gasket, and then the gasket and spring were placed in turn, and the negative electrode shell was buckled, and the battery was packaged using a battery packaging machine to obtain a modified Cu / / ZFA-1@Zn / / half-cell.

[0065] The manganese-based positive electrode, the electrode pieces cut from ZFA-1 as the negative electrode and the separator are assembled into the shell, and the electrolyte is injected. The electrolyte is composed of 2M ZnSO4 and packaged as a ZFA-1@Zn / / zinc salt / / manganese-based positive electrode aqueous zinc ion battery.

[0066] By assembling the battery in the above manner, the application of the zinc ion battery anode material in the aqueous zinc ion battery is completed.

[0067] Example 2 The main differences from Example 1 are: 1. Preparation of negative electrode materials The etching time is 1 min, and the zinc ion battery anode material with stripe arrays obtained after etching is finally recorded as ZFA-2.

[0068] 2. Assemble the battery The ZFA-2 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0069] Example 3 The main differences from Example 1 are: 1. Preparation of negative electrode materials The zinc foil was cut into 10cm×10cm zinc sheets; the hydrochloric acid concentration was 0.5mol / L. The etching time was 10min; the drying temperature was controlled at 70℃ and the drying time was 8h, and finally the stripe array zinc ion battery anode material after etching was obtained, which was recorded as ZFA-3.

[0070] 2. Assemble the battery The ZFA-3 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0071] Example 4 The main differences from Example 1 are: 1. Preparation of negative electrode materials The zinc foil was cut into 10cm×10cm zinc sheets; the hydrochloric acid concentration was 0.5mol / L. The etching time was 20min; the drying temperature was controlled at 50℃ and the drying time was 12h, and finally the stripe array zinc ion battery anode material after etching was obtained, which was recorded as ZFA-4.

[0072] 2. Assemble the battery The ZFA-4 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0073] Comparative Example 1 Bare zinc without etching 1. Preparation of negative electrode materials The zinc foil was cut into 5cm×5cm zinc sheets, and then flattened. The zinc foil was soaked in hydrochloric acid for 30s to remove the oxide film and impurities on the surface. The concentration of hydrochloric acid was 0.1mol / L. The soaking time should not be too long to avoid reducing the thickness of the zinc foil. The zinc sheet after ultrasonic treatment was taken out, and repeatedly washed with anhydrous ethanol and deionized water to remove the hydrochloric acid on the surface. It was dried in a natural environment to obtain bare zinc (Bare Zn) without etching, which was used as the zinc negative electrode material of this comparative example.

[0074] 2. Assemble the battery The zinc negative electrode material (bare zinc) prepared in this comparative example was cut into pole pieces with a diameter of 12 mm using a slicer, and two identical pole pieces were selected. One of the pole pieces was placed in the positive electrode shell, and a glass fiber diaphragm was placed. 300uL of 2M ZnSO4 was dripped as an electrolyte using a pipette, and then another pole piece was placed on top of the diaphragm. Then, the gasket and the shrapnel were placed in sequence, and finally the negative electrode shell was buckled, and the battery was packaged using a battery packaging machine, and a modified zinc negative electrode aqueous zinc ion symmetrical button battery was obtained, which was marked as a Zn / / Zn symmetrical button battery.

[0075] As above, the prepared zinc negative electrode material is cut into electrodes with a diameter of 12 mm using a slicer, and the copper foil and the treated zinc foil are used as the positive electrode and the negative electrode, respectively. The copper positive electrode is placed in the positive electrode shell, and the glass fiber diaphragm is placed. 120uL of 2M ZnSO4 is dripped as the electrolyte using a pipette, and then the zinc negative electrode is placed on top of the diaphragm. Then, the gasket and the shrapnel are placed in turn, the negative electrode shell is buckled, and the battery is packaged using a battery packaging machine to obtain a modified Cu / / Zn / / half-cell.

[0076] The manganese-based positive electrode, zinc sheet negative electrode and diaphragm are assembled into the shell, and the electrolyte is injected. The electrolyte is composed of 2M ZnSO4 and is packaged as a Zn / / zinc salt / / manganese-based positive electrode aqueous zinc ion battery.

[0077] Comparative Example 2 Differences from Example 1: 1. Preparation of negative electrode materials No ultrasonic treatment was performed during the etching process. Finally, a zinc ion battery anode material with stripe arrays after etching was obtained, which was recorded as ZFA-5.

[0078] 2. Assemble the battery The ZFA-5 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0079] Comparative Example 3 Differences from Example 1: 1. Preparation of negative electrode materials The concentration of the H3PO4 solution was 50%, and finally a zinc ion battery anode material with a stripe array after etching was obtained, which was recorded as ZFA-6.

[0080] 2. Assemble the battery The ZFA-6 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0081] Comparative Example 4 1. Preparation of negative electrode materials The acid solution used for etching is a mixed acid with a molar mass ratio of phosphoric acid to oxalic acid of 10:1.

[0082] Finally, the zinc ion battery anode material with an etched stripe array is obtained, which is denoted as ZFA-7.

[0083] 2. Assemble the battery The ZFA-7 obtained in this example is cut into pole pieces, and the battery is assembled according to the assembly steps of the battery in Example 1.

[0084] Data Analysis 1: Figure 1 The microstructure of the anode materials of Examples 1, 2 and 3 was scanned using a scanning electron microscope.

[0085] The microstructure of ZFA-1 prepared in Example 1 (such as Figure 1 A1 in Figure 1 A2 and Figure 1 ).

[0086] The microstructure of ZFA-2 prepared in Example 2 is as follows: Figure 1 B1 in Figure 1 B2 and Figure 1 As shown in B2.

[0087] The microstructure of ZFA-3 prepared in Example 3 is as follows: Figure 1 C1 in Figure 1 C2 in Figure 1 C3 in.

[0088] Conclusion 1 By comparison, it can be seen that the ZFA-1 prepared in Example 1 has a uniform morphology and clear and obvious stripes, while the ZFA-2 and ZFA-3 prepared in Example 2 and Example 3 have relatively uneven morphologies and blurred and unclear stripes.

[0089] Conclusion 2 The stripe etching depth obtained by etching the ZFA-1 prepared in Example 1 is about 0.6-0.7 µm, the gap width between the stripes is about 0.3-0.4 µm, and the length of the stripes is about 8-10 µm.

[0090] The stripe etching depth obtained by ZFA-2 etching is about 0.1µm, the gap width between stripes is about 0.1µm, and the length of the stripes is about 2-~3µm.

[0091] The stripe etching depth obtained by ZFA-3 etching is about 0.3-0.4µm, the gap width between stripes is about 0.3-0.4µm, and the length of the stripes is about 8-10µm.

[0092] Conclusion 3 Figure 1 Figure D in the figure is the SEM image of comparative example 1, and it can be seen that the surface of the zinc foil is slightly uneven; Figure 1 Figure E shows the etched material without ultrasonic treatment. The gas produced by the reaction covers the surface of the zinc foil and lifts it out, interrupting the reaction and causing the etched stripes to be lighter.

[0093] Figure 1 Figure F shows the material etched by a 50% H3PO4 solution. Due to the decrease in concentration, the reaction is incomplete and the etching depth of the stripes obtained is shallow.

[0094] Figure 1 Figure G shows the material etched by mixed acid, and the surface stripes are etched shallowly and unevenly.

[0095] Conclusion 4 The modified negative electrodes of Examples 1, 2, and 3 and Comparative Examples 2 and 3 were subjected to electrochemical tests, including constant current charge / discharge (GCD), electrochemical impedance spectroscopy (EIS), and full battery measurements.

[0096] Under the same test conditions, the polarization voltage and cycle stability of the pole pieces obtained with different reaction (etching) times are different. According to the test, the present invention achieves the longest cycle time under the condition of Example 1.

[0097] Data Analysis 2: Figure 2 , Figure 3 In the process, the negative electrodes of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were assembled into symmetrical batteries to carry out cycle performance testing.

[0098] The ZFA-1 anode prepared by etching a striped zinc array on the (002) crystal plane on the surface of the zinc anode remained stable during the battery cycle and showed good stability at a current density of 1 mA cm -2 , deposition capacity is 1 mAh cm -2 It can be cycled for 360 hours and the polarization voltage remains almost unchanged.

[0099] The etched ZFA-2 can be cycled for 180 hours; The etched ZFA-3 can be cycled for 200 hours; The ZFA-5 formed by etching (uneven morphology, unclear and unobvious stripes) can be cycled for 100 hours; The unetched zinc anode (Bare Zn) can only cycle for 45 hours before short circuiting.

[0100] In practice, the constructed interfacial layer ZFA exhibits stability and long cycle life. In some examples, at a current density of 0.5 mA cm -2 , deposition capacity is 0.5 mAh cm -2 It can even cycle for 1800 hours.

[0101] Data Analysis 3: like Figure 4 As shown in Figure 2, under a constant overpotential of -150 mV, the current of the Bare-Zn electrode continued to increase within 400 s, indicating that Zn 2+ Disordered two-dimensional diffusion occurs on the surface of the zinc negative electrode, and zinc is deposited at the location where nucleation is most likely to occur. During long-term cycles, zinc ions aggregate and grow to form dendrites.

[0102] Compared with Bare-Zn, the current of the ZFA-1 electrode (i.e., after etching / acid etching in this example) becomes stable in a very short time and maintains a lower current.

[0103] This indicates that zinc ions begin to diffuse stably in three dimensions after a short two-dimensional diffusion on the negative electrode surface. The short two-dimensional diffusion time indicates that Zn 2+ It can be reduced to Zn in a relatively fast time, thus ensuring the in-situ deposition of zinc and slowing down the growth of dendrites.

[0104] Data Analysis 4: pass Figure 5 The electrochemical impedance spectroscopy (EIS) curve of the assembled symmetrical battery shows that it has a smaller impedance than that of the unmodified zinc foil ZFA-1.

[0105] Compared with the conventional negative electrode material in comparative example 1, the negative electrode material of the aqueous zinc ion battery prepared in example 1 of the present invention has a reduced Zn 2+ The transfer resistance of ions is smaller than that of ions, and a smaller transfer resistance can promote faster charge transfer and promote Zn 2+ Ion deposition kinetics at the zinc anode.

[0106] Data Analysis 5: Figure 6 Linear sweep voltammetry (LSV) tests were performed on Zn / / Cu half-cells to verify the inhibitory effect of the ZFA-1 protective layer on the hydrogen evolution reaction. Figure 6 It can be seen that at the same voltage, ZFA-1 has a lower response current, and the lower hydrogen evolution potential improves the electrochemical performance of the battery and inhibits dendrite growth, hydrogen evolution and various side reactions.

[0107] Data Analysis 6: Figure 7Cyclic voltammetry test (CV, scan rate is 0.5 mV / s) curves of the full batteries in Example 1 and Comparative Example 1.

[0108] The horizontal axis is voltage (Voltage, unit is V), and the vertical axis is current (Current, unit is mA).

[0109] It can be seen that the two CV curves have basically the same shape, with obvious oxidation peaks and reduction peaks, and the modified electrode and the bare zinc electrode present similar redox curves, indicating that the introduced ZFA-1 protective layer, while playing a protective role, does not participate in the electrochemical reaction of charging and discharging in the battery, and therefore does not affect the electrochemical reaction of the battery.

[0110] Data Analysis 7: Figure 8 The cycle performance of the full battery assembled with the negative electrodes of Example 1 and Comparative Example 1 was tested. Example 1 at 1000mA g -1 At a current density of 1.5 2000 cycles, the discharge capacity reached a maximum of 136.9 mAh g -1 , the average Coulombic efficiency is close to 100%, and the capacity retention is about 92.3%.

[0111] Experiments have shown that the modified electrode exhibits a uniform zinc stripping / plating process and has good cycle stability.

[0112] The above describes in detail the structure, features and effects of the present invention based on the embodiments shown in the drawings. The above are only preferred embodiments of the present invention, but the present invention is not limited to the scope of implementation shown in the drawings. Any changes made according to the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the description and drawings, should be within the protection scope of the present invention.

Claims

1. A method for manufacturing anode materials for zinc ion batteries, characterized in that: include: The zinc foil is fixedly immersed in an etching solution under ultrasonic treatment with the surface having the (002) crystal plane facing upward, and the surface is etched to form a stripe array.

2. The method according to claim 1, characterized in that Before immersing the zinc foil in the etching solution, the method further comprises: A protective layer is provided on the back side of the zinc foil opposite to the surface to prevent the back side from being etched during the etching process.

3. The method according to claim 2, characterized in that The method for manufacturing a protective layer on the back side comprises: A polymer material is coated on the back surface and cured.

4. The method according to claim 1, characterized in that The etching solution is a medium-strong acid.

5. The method according to claim 4, characterized in that The medium-strong acid includes one or more of phosphoric acid, tartaric acid, sulfurous acid, pyruvic acid, oxalic acid and nitrous acid.

6. The method according to claim 1, characterized in that The etching solution is phosphoric acid, and the concentration of phosphoric acid is 50wt% to 85wt%; And / or, the surface undergoes a pretreatment to remove the surface oxide layer and the organic phase.

7. A zinc ion battery anode material obtained by implementing the method according to any one of claims 1 to 6, characterized in that: The anode material has a stripe array uniformly formed on a (002) crystal plane, and the stripes have clear outlines.

8. The zinc ion battery anode material according to claim 8, wherein The depth of the stripes is 0.6µm~0.7µm, the width of the gap between the stripes is 0.3µm~0.4µm, and the length of the stripes is 8µm~10µm.

9. An ion battery anode material, characterized in that: include: An anode metal foil, the surface of which has a selected crystal plane determined depending on the element composition of the anode metal, and the crystal plane is formed with a nano-fine structure.

10. A finished product, characterized in that: An anode material comprising any one of claims 1 to 10; Optionally, the finished product is an electrode slurry, an electrode sheet, a battery, or a power source; or, the finished product includes a container, and a power source contained in the container and made of the anode material.